Oxford dictionary of finance and banking - Brindley, Barry (Oxford ; New York : Oxford University Press, 2005)
A dictionary of finance and banking with 5000 entries with up-to-date coverage of the vocabulary used in banking, money markets, foreign exchanges, financial futures and options, commodity markets, and takeovers and mergers.
Rev. ed. of: A dictionary of finance. 2nd ed. 1997.
"Contributors, Barry Brindley ... [et al.]"--6th prelim. p.
"A companion volume to A dictionary of business and A dictionary of accounting"--Pref.
sju 21/03/2019
Ref.
Keywords: Finance; Banks and banking